2020
DOI: 10.1002/sej.1376
|View full text |Cite
|
Sign up to set email alerts
|

Do policy makers take grants for granted? The efficacy of public sponsorship for innovative entrepreneurship

Abstract: Research Summary We investigate the short‐ and long‐term effects of public sponsorship in the form of grants on venture growth and subsequent investment funding. We adopt a temporal approach and assess our results using discontinuous growth modeling. This approach allows us to unpack the complexity of sponsorship interventions and provide insights into how quickly, how long, and under what conditions grants augment growth. Using a proprietary sample of 129 ventures located in eight incubators, we find that sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 114 publications
1
26
0
Order By: Relevance
“…Scholars agree that funding opportunities determine the innovation success of SMEs by increasing the level of innovation activities, output performance, productivity, and competitiveness [28,46,52,57]. The novelty of this research lies in its quantitative evaluation of innovation policy programs using a methodology that examines the direct relationship between public funding and an increase in the operating revenues of the beneficiary SMEs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scholars agree that funding opportunities determine the innovation success of SMEs by increasing the level of innovation activities, output performance, productivity, and competitiveness [28,46,52,57]. The novelty of this research lies in its quantitative evaluation of innovation policy programs using a methodology that examines the direct relationship between public funding and an increase in the operating revenues of the beneficiary SMEs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, subsidies have a positive and significant treatment effect on new technology-based enterprises' total factor productivity growth, but only if subsidies are provided competitively and are targeted to increase R&D investments. The authors in [52] used a proprietary sample of 129 startups located in eight incubators to find that securing an early grant enhances the rate at which initiatives gain private investment capital but not revenue over time. The authors in [53] revealed that subsidies are an important policy instrument in encouraging young innovative companies to develop inventions.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The type of support also matters, whether it comes through training, funding, or advising, as exemplified in the article of Astebro and Hoos (2021). Policy treatments may also impact recipient ventures in differential ways, as exemplified by Stevenson, Kier, and Taylor's (2021) findings that public grants may enhance the likelihood of receiving subsequent (private) investments, but also negatively affect the venture's revenue growth over time. These are examples of the thorny issues and potential tradeoffs for policymakers and researchers evaluating conditions under which successful policies can outweigh potential costs and crowding‐out effects on firms not included in policy initiatives.…”
Section: Research Frameworkmentioning
confidence: 99%
“…They highlight several themes from our macro–micro policy integration framework and wrestle with the tradeoffs associated with policy interventions. Two focus on macro themes (Teodorescu & Kuhn, 2021; Wang, Malik, and Wales, 2021), two address micro themes (Astebro & Hoos, 2021; Stevenson, Kier, & Taylor, 2021), and two incorporate elements of both (Lamine, et al, 2021; Murtinu, 2021).…”
Section: The Papers In the Special Issuementioning
confidence: 99%
See 1 more Smart Citation